2023
DOI: 10.3390/su15043189
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Use of Extracts of Some Plants Growing in Ethiopia for the Formulation of Herbal Shampoo and Its Antimicrobial Evaluation

Abstract: Shampoo prepares surfactants to remove dirt, surface grease, and skin debris from hair, shaft, and scalp without harming the user. This study aimed to formulate herbal shampoo using Ethiopian plant extracts and evaluate their quality parameters. Herbal shampoos were formulated using seed oil extracts of Lepidium sativum L. and Ricinus communis L., and essential oil extracts of Lippia adeonsis Hochst ex. Walp koseret, along with other ingredients. The formulated herbal shampoos were evaluated for their organole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The prepared shampoo as shown in the Figure 9 was opaque, light brown in color, and had pleasant odor due to incorporated rose oil in the formulation. The pH of shampoo was 6.9, which is within the recommended pH range for a shampoo that is 5–7.8 45 . The prepared shampoo produced stable foam of 35 mL as shown in Figure 10.…”
Section: Resultsmentioning
confidence: 65%
“…The prepared shampoo as shown in the Figure 9 was opaque, light brown in color, and had pleasant odor due to incorporated rose oil in the formulation. The pH of shampoo was 6.9, which is within the recommended pH range for a shampoo that is 5–7.8 45 . The prepared shampoo produced stable foam of 35 mL as shown in Figure 10.…”
Section: Resultsmentioning
confidence: 65%
“…Furthermore, the interest of natural product-based drug discovery over high throughput screening of combinatorial libraries [18] justifies the suitability of natural compound pharmacophores in the discovery of antiprotozoal drugs. Lippia adoensis is an example of medicinal plants used for the traditional treatment of several diseases, including skin disorders, superficial fungal infections, malaria, and fever conditions [19]. In Ethiopia, the leaves of Lippia adoensis are used to cure toothache, diarrhea and indigestion [20], whereas the leaf decoction is employed as a remedy for fever and constipation in children, and for the treatment of bronchitis, skin disorders and ophthalmia [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…More consumers prefer to use plant-based hair shampoos, which are natural and sustainable. Godeto et al [2] recently reported that formulated herbal shampoos could also be on par with commercially available shampoos. The shampoo formulations were pleasant, producing good foaming and cleansing abilities.…”
Section: Introductionmentioning
confidence: 99%